Physiological and structural aspects of fruit and vegetable mild processing - Panarese, Valentina <1984> (Alma Mater Studiorum - Università di Bologna, 2013)

(untitled)
Over the past years fruit and vegetable industry has become interested in the application of both osmotic dehydration and vacuum impregnation as mild technologies because of their low temperature and energy requirements. Osmotic dehydration is a partial dewatering process by immersion of cellular tissue in hypertonic solution. The diffusion of water from the vegetable tissue to the solution is usually accompanied by the simultaneous solutes counter-diffusion into the tissue. Vacuum impregnation is a unit operation in which porous products are immersed in a solution and subjected to a two-steps pressure change. The first step (vacuum increase) consists of the reduction of the pressure in a solid-liquid system and the gas in the product pores is expanded, partially flowing out. When the atmospheric pressure is restored (second step), the residual gas in the pores compresses and the external liquid flows into the pores. This unit operation allows introducing specific solutes in the tissue, e.g. antioxidants, pH regulators, preservatives, cryoprotectancts. Fruit and vegetable interact dynamically with the environment and the present study attempts to enhance our understanding on the structural, physico-chemical and metabolic changes of plant tissues upon the application of technological processes (osmotic dehydration and vacuum impregnation), by following a multianalytical approach. Macro (low-frequency nuclear magnetic resonance), micro (light microscopy) and ultrastructural (transmission electron microscopy) measurements combined with textural and differential scanning calorimetry analysis allowed evaluating the effects of individual osmotic dehydration or vacuum impregnation processes on (i) the interaction between air and liquid in real plant tissues, (ii) the plant tissue water state and (iii) the cell compartments. Isothermal calorimetry, respiration and photosynthesis determinations led to investigate the metabolic changes upon the application of osmotic dehydration or vacuum impregnation. The proposed multianalytical approach should enable both better designs of processing technologies and estimations of their effects on tissue. === Negli ultimi anni l'industria di trasformazione al minimo ha mostrato un crescente interesse verso i trattamenti di disidratazione osmotica e di impregnazione sottovuoto per le loro caratteristiche basse temperature di processo e per le relativamente contenute esigenze energetiche. La disidratazione osmotica, che consiste nell'immersione di tessuti vegetali in soluzioni ipertoniche, consente all’acqua presente nei tessuti di diffondere nella soluzione osmotica ed ai soluti in soluzione di diffondere, in direzione opposta, all'interno dei tessuti. L'impregnazione sottovuoto prevede l’immersione del tessuto vegetale in una soluzione di processo e consiste di due fasi successive. Durante la prima fase, la riduzione della pressione agente sul sistema solido-liquido provoca l'espansione ed il parziale rilascio nella soluzione del gas contenuto nei pori del tessuto. La seconda fase di ripristino della pressione atmosferica determina l’espansione del gas residuo nel tessuto con conseguente richiamo della soluzione esterna all'interno dei pori. L’impregnazione sottovuoto rappresenta un’interessante operazione tecnologica poiché può permette l’introduzione nei tessuti di specifiche molecole quali antiossidanti, regolatori di pH, stabilizzanti o crioprotettori. Il presente studio si è proposto di valutare, seguendo un approccio multianalitico di indagine, le principali modificazioni a carico di tessuti vegetali assoggettati a trattamenti di disidratazione osmotica o impregnazione sottovuoto. Misurazioni di tipo macro- (risonanza magnetica nucleare), micro- (microscopia ottica) ed ultrastrutturali (microscopia elettronica a trasmissione) sono state affiancate ad analisi di texture e di calorimetria a scansione differenziale. Sono stati valutati i principali effetti sulle interazioni aria-liquido in reali condizioni, sullo stato dell'acqua del tessuto e sui compartimenti cellulari. Misurazioni di calorimetria in isoterma e determinazioni dell'attività respiratoria e fotosintetica hanno infine permesso un'indagine dei cambiamenti metabolici. Tale approccio multianalitico, permettendo una valutazione complessiva delle modificazioni a carico della materia prima, può essere applicato nell’ottimizzazione dei parametri di processo sulla base delle caratteristiche ricercate nel prodotto finito.